Natriuretic peptide‐based inclusion criteria in heart failure with preserved ejection fraction clinical trials: insights from PARAGON‐HF. (14th February 2022) - Pabón, Maria A.; Cunningham, Jonathan W.; Claggett, Brian L.; Packer, Milton; Zile, Michael; Pfeffer, Marc A.; Lefkowitz, Martin; Shi, Victor; Rizkala, Adel; McMurray, John J.V.; Solomon, Scott D.; Vaduganathan, Muthiah
Abstract : Aim: Natriuretic peptides (NPs) are now routinely incorporated as key inclusion criteria in clinical trials of heart failure with preserved ejection fraction (HFpEF) as objective measures of risk. An early amendment in PARAGON‐HF required all participants to have elevated NP concentrations, but some were enrolled pre‐amendment, providing a unique opportunity to understand the influence of enrolment pathway in HFpEF clinical trials. Methods and results: Among 4796 participants in PARAGON‐HF, 193 (4.0%) did not meet the final NP‐based enrolment criteria (N‐terminal pro‐B‐type natriuretic peptide >300 pg/ml for patients in sinus rhythm or >900 pg/ml for patients in atrial fibrillation/flutter). These patients had lower rates of the primary endpoint of total heart failure hospitalizations and cardiovascular death as compared with patients meeting final enrolment criteria (8.6 [6.7–11.2] events per 100 patient‐years vs. 14.0 [13.4–14.7] events per 100 patient‐years; p  = 0.01). The rate ratio for the treatment effect comparing sacubitril/valsartan with valsartan was 0.85 (95% confidence interval 0.74–0.99; p  = 0.04) in those who met final criteria. Conclusions: Natriuretic peptides are an important tool in HFpEF clinical trials to objectively affirm diagnoses and enrich clinical event rates.